Synthesis of (-)-cannabidiol (CBD),(-)-Δ9- and(-)--Δ8-tetrahydrocannabinols, encapsulation of CBD with nanoparticles for controlled delivery and biological evaluation - Moya-Utrera, Federico; Fuentes-Ríos, David; Romero-Carrasco, Antonio; Doña Flores, Manuel; Cheng-Sánchez, Iván; Díaz-Morilla, Amelia; Pino-González, María Soledad; Martínez-Férez, Antonio; Moreno, Javier; Mesas, Cristina; Melguizo, Consolación; Prados, José; et al. (Wiley, 2024)
Cannabidiol (CBD) is garnering increasing interest due to its significant biological activity. This natural compound is one of the major cannabinoids in Cannabis sativa L. In this work, we describe the encapsulation of CBD in solid and hollow pH-sensitive poly(4-vinylpyridine) (solid@p4VP and hollow@p4VP) nanoparticles, and temperature-sensitive poly(N-isopropylacrylamide) (solid@pNIPAM and hollow@pNIPAM) nanoparticles for transport and release CBD in a controlled manner. The CBD loading into these smart polymeric systems was effective and their release profiles, solubility and resistance to stomach and intestinal conditions were evaluated, showing satisfactory properties and improved bioavailability with respect to free CBD. Finally, the A549 human lung cancer cell line was used as lung adenocarcinoma epithelial cellular model to carry out preliminary assays of the in vitro activity of the vehiculized CBD. For all these studies, synthetic CBD was employed, for which a new efficient and scalable synthesis of cannabinoids has been developed.
Keywords: Cannabinoides - Síntesis; Cannabidiol